The therapeutic potential of carnosine: Focus on cellular and molecular mechanisms - Giuseppe Caruso; Lucia Di Pietro; Vincenzo Cardaci; Salvatore Maugeri; Filippo Caraci (Elsevier, 2023)
Carnosine is a naturally occurring endogenous dipeptide composed by the ligation of β-alanine and L-histidine performed particularly by tissues with an increased oxidative metabolism such as muscles and brain. In the last 50 years different studies have assessed the role and function of carnosine through numerous in vitro, in vivo, and clinical studies, demonstrating the multimodal mechanism of action of this dipeptide that includes anti-aggregant, antioxidant, and anti-inflammatory activities. In particular its activity has been investigated in experimental models of cardiovascular disease (CVD), type 2 diabetes mellitus (T2DM), and neurodegenerative disorders, such as cerebral ischemia and Alzheimer's disease (AD). In the present review, we examined the protective role that carnosine could exert in the context of T2DM, CVD, and AD, which show common pathogenic mechanisms including oxidative stress, inflammation, and aggregation phenomena. Carnosine's pharmacodynamic profile is multimodal and combines the systemic anti-inflammatory and antioxidant activities with its anti-aggregant and neuroprotective efficacy in the central nervous system. This enlarged pharmacological activity opens a new path to explore the therapeutic potential of carnosine in all the three diseases, and in particular in patients with T2DM, who often show a history of CVD and also have an increased risk to develop mild cognitive impairment and AD.